Gender stereotypes in Malaysian Parliament: A content analysis - Ngeow, Y.M.; David, M.K.; David, S.C.Y. (2010)
This study examines the use of sexist language and gender stereotypes in the parliamentary debates in the Malaysian parliament. Given the prevalence of the majority male Members of Parliament (MPs) as well as their dominance in the Parliament, this study discusses and analyses patterns of gender stereotyping and the social implications arising from their discourse.